2017
DOI: 10.1002/jum.14499
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Delineation of Tarsal Tunnel Innervation via Ultrasonography

Abstract: On the basis of this work, we can conclude that high-resolution US is almost 100% effective as a tool for identifying the tibial nerve and its branches, enabling the specialist to make diagnoses or perform selective treatments on each nerve branch and even to design surgical interventions by observing the patient's anatomy before performing the dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
2
23
1
1
Order By: Relevance
“…It is necessary that the operators are familiar with the anatomy and know the possible anatomic variants of this region. We have recently shown that with proper training and the use of high‐resolution equipment, it is possible to correctly identify branches of the TN as small as 1 mm in diameter . Although this has not been our practice, surgeons may consider forming a team with a radiologist or seeking assistance from a sonographer to accelerate his or her learning curve, at least during the initial stages of training.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is necessary that the operators are familiar with the anatomy and know the possible anatomic variants of this region. We have recently shown that with proper training and the use of high‐resolution equipment, it is possible to correctly identify branches of the TN as small as 1 mm in diameter . Although this has not been our practice, surgeons may consider forming a team with a radiologist or seeking assistance from a sonographer to accelerate his or her learning curve, at least during the initial stages of training.…”
Section: Discussionmentioning
confidence: 99%
“…The MPN is released by using the protocols with the instruments and US control as described for TN release. The bifurcation of the TN into the MPN and LPN should be mapped and its route drawn on the skin . A safe entry point is located by using US to avoid vascular damage to the deeper layers immediately proximal to the AHM.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations